Identification of a novel HEXB Mutation in an Iranian Family with suspected patient to GM2‐gangliosidoses - Fatemeh Mansouri‐Movahed; Fatemeh Akhoundi; Parvaneh Nikpour; Masoud Garshasbi; Modjtaba Emadi‐Baygi (Clinical Case Reports, 2020)
Abstract Sandhoff disease is one of the GM2‐gangliosidoses which is caused by a mutation in the HEXB preventing the breakdown of GM2‐ganglioside. We report a novel HEXB variant in a family with a history of a dead girl with Sandhoff disease which was not found in controls.